Teaching english grammar: efficiency of inductive and deductive approaches – students’ perceptions - Nešić, Ivana D.; Hamidović, Kimeta Ć. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This paper is aimed at investigating students’ attitudes towards inductive and deductive approaches to teaching grammar of English as a foreign language. The study includes 134 students of Business School of Applied Studies in Blace. The research was conducted through a questionnaire which consists of 15 items concerning teaching English language, which students rated according to the Likert scale. At the beginning, different approaches to teaching grammar of a foreign language – inductive and deductive are presented. Namely, it has been a constant debate whether grammar rules should be explicitly explained and then practiced through numerous examples, or whether the acquisition of foreign language grammar is more efficient when students are exposed to a foreign language and, based on context and everyday situations, they induce the rules by themselves. According to the results of the questionnaire, over 70% of the students preferred the deductive approach to teaching English grammar, whereas over 40% of them acknowledged that the implicit approach is also important for grammar acquisition. Another conclusion indicates that the efficient acquisition of English grammar occurs when these two approaches are combined.